Respuestas Lectoras De Los Ninos Y Las Ninas. Conversación Literaria Y Modos De Acceso Al Poema (Global Journal of Human-Social Science, 2021)
The literary reading exercised from the collective understanding is to go attributing meanings by promoting enunciation situations in which the reader-students reconstruct the ideals that the reading presents To understand therefore is to assess the responses and intentions that underlie the background of the reading from the literary conversation as a procedure for elucidating the paths to meaning Reading is playing with everyone s experience Therefore for this activity of assertion of senses to occur precisely readers have the mission of elucidating clarifying solving the unknowns that are evoked Thus understanding will not be a unitary and homogeneous process but will become a decisionmaking process where everyone contributes and shares experience and communicate your impressions of reading and not where you blame yourself because you have not said what you are told to express In this way we propose with this work to present the different ways routes or accesses reading keys that served as the basis for the achievement of an understanding of poems in which a communicative activity of experience and creativity was generated student
Keywords: reading and comprehension; reading responses; literary conversation; access codes